Pension Fund Investment from Ageing to Emerging Markets - Fischer, Bernhard (OECD Development Centre Policy Briefs, 1995)
• The rapid ageing of populations in the rich economies can be expected to stimulate strong growth in private funded pensions, providing a massive potential of foreign finance for developing countries. • Pension managers can reap big diversification benefits by investing on the emerging stock markets of the younger economies, benefits which are largely unexploited so far. • The authorities in OECD countries should consider removing regulatory constraints imposed on pension assets that deprive retirees from the pension-improving benefits of global diversification. • Policy makers in developing countries should design policies that reassure institutional investors on default risk and stock market illiquidity, if they want to tap a higher share of OECD pension assets